Aberrant Shakespeare: Ron Athey’s Excesses, Bataille’s Solar Anus, Becomings-Macbeth - Kolodezh, Sam; Reynolds, Bryan (Multicultural Shakespeare: Translation, Appropriation and Performance, 2024)
l In this article we argue that Ron Athey’s performance Solar Anus is an aberrant adaptation of Shakespeare’s Macbeth in which the parodic world of abundant excess that the witches catalyze is redemptively captured and transformed through the playful, androgynous, and excessive performance of Athey, who fulfills the witches’ prophecy and continues to live on sovereignly as both Macbeth and Lady Macbeth. Athey is a Los Angeles-based performance artist who practices what is sometimes called “extreme performance,” exploring the limits of aesthetics and the capabilities of the human body to express both beauty and pain. His work Solar Anus draws on the works of Georges Bataille, especially his short essay-poem, Solar Anus, as well as Paul Molinier, a queer French painter and visual artist who worked on the fringes of the surrealist movement. We work through the combined sociopolitical theory, performance aesthetics, and research methodology of transversal poetics and engage especially with the theories and explorations of aesthetics and sovereignty by Georges Bataille and Gilles Deleuze and Félix Guattari in order to explore the ways in which Athey is capable of realizing the witches’ prophecy of sovereignty without being destroyed by the parodic world that they create and inhabit. Alongside the concepts of sovereignty, we examine how Bataille’s ideas of parody, sacrifice, and excess offer new ways of understanding the world of Macbeth and how excess and sovereignty both function within its porous borders.